Punishment for polluting inland water: case of corporations - Abdul Wahab, Harlida (Future Academy, 2018)
Water pollution is among the common environmental problems where industrialization is identified as one of its reasons. Industrial activities by corporations produce by-products and wastes and this has intensely caused harm to the environment. As a non-science mechanism, law and legislations function to control environmental problem by, among others, imposing punishment. This article studies the punishment for polluting water that imposed by court towards the corporations. The observations are made to the penalty’s provisions of the Environmental Quality Act 1974, the main environmental statute in Malaysia, and penalties imposed by court. The cases of water pollution are obtained from the records of Department of Environment Malaysia for a three-year period, from 2013 until 2015. The study found that there was a wide gap between the maximum punishment by law and penalties positioned by court, and the corporations opted for fines. It is therefore suggested for a stiffer and more appropriate punishment imposed on the corporations as well as individuals behind it for an effective implementation. It should not just higher fine but imprisonment can be made possible so that the law would function as a control mechanism that can curb, shape, manage and regulate the society.